2022
DOI: 10.1001/jamanetworkopen.2022.38569
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Morbidities and Time to Cancer Diagnosis Among Adults With Colon Cancer in England

Abstract: ImportanceMental health morbidity (MHM) in patients presenting with possible cancer symptoms may be associated with prediagnostic care and time to cancer diagnosis.ObjectiveTo compare the length of intervals to cancer diagnosis by preexisting MHM status in patients who presented with symptoms of as-yet–undiagnosed colon cancer and evaluate their risk of emergency cancer diagnosis.Design, Setting, and ParticipantsThis cohort study was conducted using linked primary care data obtained from the population-based C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The characteristics of the included studies are summarised in online supplemental appendix S7. The system interval was examined in 12 studies, with 7 different time points evaluated, summarised in figure 2 12–23. In total, 15 studies reported the receipt of surgery,19 20 24–36 7 studies evaluated surgical variation,37–43 14 studies reported the receipt of chemotherapy,19 20 24–27 44–51 7 reported the receipt of radiotherapy19 20 25–27 43 52 and 2 reported the receipt of any treatment 17 46…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the included studies are summarised in online supplemental appendix S7. The system interval was examined in 12 studies, with 7 different time points evaluated, summarised in figure 2 12–23. In total, 15 studies reported the receipt of surgery,19 20 24–36 7 studies evaluated surgical variation,37–43 14 studies reported the receipt of chemotherapy,19 20 24–27 44–51 7 reported the receipt of radiotherapy19 20 25–27 43 52 and 2 reported the receipt of any treatment 17 46…”
Section: Resultsmentioning
confidence: 99%
“…In total, 32 of the 41 studies adjusted or stratified for at least one other factor 12–26 32–41 44–49 51. The remaining nine studies provided unadjusted rates 27–31 42 43 50 52…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased screening may over time be associated with fewer diagnoses based on clinical presentation, but this will not remove the need for clinical vigilance, enhanced safety netting, and triage testing and appropriate referral. As we now know, 1 this is even more applicable for patients with concurrent mental health problems, who may need specific targeted interventions to improve screening uptake and symptomatic presentation to primary care.…”
Section: Openmentioning
confidence: 99%
“…In this landmark study by Benitez Majano et al, the authors use linked primary care data to study pathways to diagnosis and diagnostic delay and the association with mental health conditions. Unsurprisingly, patients with a coexistent mental health diagnosis experienced diagnostic delay.…”
mentioning
confidence: 99%